Produção científica sobre inclusão escolar de alunos com Transtorno do Espectro Autista nas revistas brasileiras de educação especial - Santana, Thaluane Sigoli (Universidade Federal de São Carlos, 2021)
In Brazil, there are two important journals in the Special Education area, the Special Education Journal (REE) edited by the Federal University of Santa Maria, created in 1987; and the Brazilian Journal of Special Education (RBEE), created in 1993, maintained by the Brazilian Association of Special Education Researchers (ABPEE). Both are of extreme relevance for research in the Special Education area, increasing the quantity and qualifying the information about the theme. The present study aimed to perform a bibliographical survey of scholar inclusion of children with Autism Spectrum Disorder (ASD) in the Brazilian Journal of Special Education (RBEE) and Special Education Journal (REE) of Santa Maria published between 2000 and 2020. This research replicated and updated the Cabral and Marin (2017) study. The bibliographical survey utilized the electronic collect data in the Scielo website for RBEE and REE's own website. The evaluated period of RBEE refers to the volumes available online since 2005 in Scielo, and for REE since 2000 available online on the magazine's website. To search for studies, Portuguese words and combined with the Boolean descriptor “and”: Inclusion and School and Autism; Inclusion and School and Autism; School and Autism. A search was also made with the same combinations, but using the expression “autistic spectrum” instead of “autism”. Thirteen scientific research were selected. The studies analyzed were published in 2008 and between 2010 e 2020 (until the data collect, October of 2020), five studies published in RBEE (years 2008, 2010, 2014, 2016, and 2018) and eight studies published in REE (years 2013, 2015, 2017, 2018, 2019 and 2020). Regarding the objectives, four studies investigated the conception of teachers about inclusive education and one of the family members; two studies carried out teacher training; three studies described strategies employed by teachers in working with students with autism, and one article described research on the schooling of people with ASD. Most of the participants were teachers, in total 352, and 25 family members. The number of participants in the studies ranged from one to 217 participants, with three studies had between one and two participants; three studies had between 4 and 12 participants; four studies had between 20 and 58 participants and one study had 217 participants. In general, studies have shown that one of the main factors for inclusion is to rethink the school with different pedagogical attitudes and practices, and also to offer training and specific support to teachers. Future research should invest in evaluating the effects of specific interventions for the development and learning of students with autism.
Scientific production about the school inclusion of students with Autism Spectrum Disorder in brazilian special education magazines
Keywords: Inclusão social; Transtorno do Espectro Autista; Educação especial; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO